PENGEMBANGAN MODUL PRAKTIKUM IPA-FISIKA BERBASIS INKUIRI UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS PADA MATERI GETARAN DAN GELOMBANG DI KELAS VIII MTS AL-JIHAD PONTIANAK - warsinah warsinah; Matsun Matsun; Syarif Lukman Hakim Alsegaf (IKIP PGRI Pontianak, 2022)
The purpose of this research is to develop an inquiry-based Science-Physics Practicum Module on Vibration and Waves material to improve students' science process skills. The design in this study uses the Borg Gall development model which is modified into six research stages, namely: 1) potential and problems 2) data and information collection 3) product design 4) Design validation 5) Design revision 6) Product trial. This research was conducted at MTs Al-Jihad Pontianak. The subjects in this study were the subject of development (Validator) and the subject of product testing (students) for class VIII A, amounting to 17 students. Based on the results of data analysis, it can be seen that 1) Inquiry-based Science-Physics practicum module based on material expert assessment with an average score of 73% with appropriate criteria and based on media expert assessment with an average score of 75% with appropriate criteria, 2) Student responses to Inquiry-based Science-Physics practicum module with an average score of 79% with criteria strongly agree, 3) The value of students' science process skills after using the Inquiry-based Science-Physics practicum module increased from each aspect. The aspect of observing with an average score of 92% with very good criteria, aspects of predicting with an average score of 70% with good criteria, aspects of clarifying with an average score of 76% with very good criteria, aspects of communicating with an average score of 77% with very good criteria, measuring aspects with an average score of 94% with very good criteria.